Network pharmacology and molecular docking approaches of Astaxanthin (ATX) against atherosclerosis - Barizi, Anis Zuhaida Mamnun; Shamsol Azman, Ain Nabila Syahira; Saad, Muhamad Fikri Shazlan; Abdullah, Muhammad Nazrul Hakim; Lim, Vuanghao; Yong, Yoke Keong (Wolters Kluwer - Medknow Publications and Media, 2024)
Background: Atherosclerosis is an inflammatory disease well known as the leading cause of Cardiovascular Diseases (CVDs). Astaxanthin (ATX) is a reddish pigment that belongs to the family of xanthophylls, which are oxygenated derivatives of carotenoids. Aim: In this study, we aimed to investigate the targets and mechanisms involved in treating atherosclerosis using network pharmacology and molecular approaches. Materials and Methods: The genes targeted by ATX were predicted using Swiss Target Prediction, BATMAN-TCM, and Super-Pred databases, while genes associated with atherosclerosis were retrieved from DigSee, GAD, GeneCards, and OMIM databases. The interactions between ATX and atherosclerosis genes were identified through protein–protein interaction analysis, Gene Ontology (GO) enrichment analysis, and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis. Results: The results revealed a total of 240 ATX-related genes and 4,977 atherosclerosis-related genes, with 172 overlapping genes identified. Six core genes were obtained: SRC, AKT1, MAPK3, HDAC1, PIK3R1, and RXRA. These results were further validated through the molecular docking approach, where all six core targets exhibit low binding energy, suggesting strong binding affinity, with PIK3R1 having the best binding affinity among them. Conclusion: Our study provides novel insights into the potential application of ATX in the management of atherosclerosis.